Strategi Pemasaran Untuk Meningkatan Partisipasi Masyarakat Dalam Pemilu Di Kabupaten Blitar Tahun 2019 - Nikmatus Solihah (Jurnal Ekonomi dan Manajemen, 2019)
Marketing strategy is an effort to market a product, whether it is goods or services, using a certain pattern of plans and tactics so that the number of sales becomes higher. Definition of marketing strategies can also be interpreted as a series of efforts made by the company in order to achieve certain goals, because the potential for selling propositions is limited to the number of people who know this. Marketing Strategy has an important role in a company or business because it serves to determine the economic value of the company, both the price of goods and services. One of the most fundamental elements and indicators of the success and quality of the implementation of democratic elections is the active involvement of the community in the process of the stages of elections, especially in terms of monitoring or monitoring the electoral process. The role and participation of civil society in monitoring or monitoring the course of the democratic contestation process is very important. Participation aims to encourage active democratic activities for all electoral processes. The interest in the participation focus is an indicator of improving the quality of democracy and the nation's political life marketing strategies are implemented in the electoral organization to increase community politics and participation rates.